2022
DOI: 10.1007/s12672-022-00606-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated radiomics, dose-volume histogram criteria and clinical features for early prediction of saliva amount reduction after radiotherapy in nasopharyngeal cancer patients

Abstract: Purpose Previously, the evaluation of xerostomia depended on subjective grading systems, rather than the accurate saliva amount reduction. Our aim was to quantify acute xerostomia with reduced saliva amount, and apply radiomics, dose-volume histogram (DVH) criteria and clinical features to predict saliva amount reduction by machine learning techniques. Material and methods Computed tomography (CT) of parotid glands, DVH, and clinical data of 52 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…The augmentation of dosimetric and clinical information contributed to an improvement in AUC (91.7 %) and precision (100.0 %) values. Our findings align with previous studies [ 23 , 42 ], demonstrating that the incorporation of baseline imaging RFs with dose-volume and clinical data improves the accuracy of machine learning models in predicting radiation-induced xerostomia compared to clinical or dose-volume features alone. In contrast to the findings of Sheikh et al's study, our present study identified different top clinical features for mucositis prediction, as shown in Table 2 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The augmentation of dosimetric and clinical information contributed to an improvement in AUC (91.7 %) and precision (100.0 %) values. Our findings align with previous studies [ 23 , 42 ], demonstrating that the incorporation of baseline imaging RFs with dose-volume and clinical data improves the accuracy of machine learning models in predicting radiation-induced xerostomia compared to clinical or dose-volume features alone. In contrast to the findings of Sheikh et al's study, our present study identified different top clinical features for mucositis prediction, as shown in Table 2 .…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have indicated that radiomics can be a valuable tool to facilitate precision diagnosis, treatment planning, and predicting outcomes [ 22 ]. In recent years, it has been shown that integrating quantitative medical imaging biomarkers into clinical and dosimetric data has improved the prediction of radiation-induced toxicities in the treatment of various cancers [ 19 , [23] , [24] , [25] , [26] ]. Moreover, the advances in AI, principally machine learning models, have boosted the potential of the typically high-dimensional quantitative radiomics features (RFs) in predicting RT-induced toxicity [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%